2013
DOI: 10.1142/s2010007813500048
|View full text |Cite
|
Sign up to set email alerts
|

Do Geographical Variations in Climate Influence Life-Satisfaction?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…In addition, rainfall also exerts a significant negative effect on reported levels of well-being and the authors argue that the effects of climate change-as reported by the IPCC-might lead the positive well-being effect for the majority of the Russian population. Other studies by Becchetti et al (2007), Kööts et al (2011) and Murray et al (2013) also find evidence that temperature, sunshine, humidity, fog, rain are related to indicators of happiness, life satisfaction and affective experiences, and thus, there seems to be a growing body of literature that suggests that weather patterns influence the way we react and perceive well-being.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, rainfall also exerts a significant negative effect on reported levels of well-being and the authors argue that the effects of climate change-as reported by the IPCC-might lead the positive well-being effect for the majority of the Russian population. Other studies by Becchetti et al (2007), Kööts et al (2011) and Murray et al (2013) also find evidence that temperature, sunshine, humidity, fog, rain are related to indicators of happiness, life satisfaction and affective experiences, and thus, there seems to be a growing body of literature that suggests that weather patterns influence the way we react and perceive well-being.…”
Section: Literature Reviewmentioning
confidence: 90%
“…() and Murray et al . () also find evidence that temperature, sunshine, humidity, fog, rain are related to indicators of happiness, life satisfaction and affective experiences, and thus, there seems to be a growing body of literature that suggests that weather patterns influence the way we react and perceive well‐being.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…They comprise air pollution (Welsch, 2002(Welsch, , 2006Luechinger, 2009;MacKerron and Mourato, 2009;Ferreira and Moro, 2010;Levinson, 2012), airport noise (Van Praag and Baarsma, 2005), climate parameters (Rehdanz and Maddison, 2005;Maddison and Rehdanz, 2011;Murray et al, 2013), flood events (Luechinger and Raschky, 2009), and drought events (Carroll et al, 2009). Kimball et al (2006) investigated changes in happiness for US adults after hurricane Katrina.…”
Section: Economics and Subjective Well-beingmentioning
confidence: 99%
“…Smyth et al (2008) use pollution data in 30 cities in urban China, and also find a clear negative impact of SO 2 emission on subjective well-being. MacKerron and Mourato (2009) A recent paper by Murray et al (2011) considers the regional variation of climate across Europe and its impact on life satisfaction for the third wave of the European Values Survey. However, it does not consider air pollution, which, at least in the medium-run, is more amenable to policy intervention than climate.…”
Section: Introductionmentioning
confidence: 99%